2012
DOI: 10.4172/2168-9431.1000102
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Immunotherapy Strategies in Colorectal Cancer Treatment

Abstract: The colorectal cancer (CRC) is a most frequent cause of cancer-related deaths. Surgical tumor resection remains the primary curative treatment for CRC but nearly 50% of patients with macroscopic clearance of the tumor by surgery relapses. For this purpose new complementary treatments, such as immunotherapy, are being explored. In this article, we analyze and discuss the clinical immunotherapy vaccine studies performed in patients treated for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…These treatments have resulted in significant benefits to patients with the majority of tumor types, and the clinical outcomes have become more satisfactory (24). To further increase this trend of improving treatment outcomes, new treatments are necessary; one option proposed for this is immunotherapy (5). It is recognized that multidisciplinary treatments should be used in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments have resulted in significant benefits to patients with the majority of tumor types, and the clinical outcomes have become more satisfactory (24). To further increase this trend of improving treatment outcomes, new treatments are necessary; one option proposed for this is immunotherapy (5). It is recognized that multidisciplinary treatments should be used in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in 186 patients showed the safety of the vaccine, a high immunological response to the peptide and, most importantly, the potential clinical advantage of the vaccine [17]. Immunization with the E75 vaccine in combination with a granulocyte colony stimulating factor (G-CSF) correlated with higher rates of recession-free survival and a lower relapse rate [18].…”
Section: Immunological Therapy Of Cancer Diseasesmentioning
confidence: 99%